School bullying as a social problem for children in light of current changes - bousakra, salima; abdelsalam, salima (Journal of Social Sciences and Humanities, 2024)
School bullying is one of the biggest social problems facing societies today. It affects a large number of students and causes them serious psychological and social problems. In addition, this type of bullying can lead to a negative impact on students’ academic performance and behavior. To solve this problem, schools and communities must work together to find effective solutions and educate students and their parents about the importance of interacting positively and respecting others. It is worth noting here that solutions to the problem of school bullying include promoting a culture of shared responsibility between teachers, students, and parents at the individual level. Teachers can also encourage students to express their thoughts and feelings in positive and non-violent ways. It is necessary to have mechanisms to report bullying and punish those involved. In addition, schools must provide psychological and social support to students who are victims and involved in bullying. This can include individual sessions with counselors or workshops to enhance positive communication and conflict resolution skills. At the collective level, schools must take firm measures to reduce bullying and promote a friendly and respectful educational environment. So, parents and society in general must be made aware of the danger of bullying and the necessity of their role in combating it. This can be achieved by organizing awareness campaigns and workshops for parents and providing resources to support schools in implementing anti-bullying programs.